(untitled) (New York, 2001)
Lange Clinical Manuals deliver medical information for common problems in an easy-to-use format. This edition focuses on the diagnosis and treatment of common primary care problems--reviews 70 of the most common complaints encountered in an outpatient setting. Covers chronic illnesses, psychiatric disorders, reproductive health, special populations, and patient-centered care. Ambulatory medicine is a "must-have" for medical students, residents, physicians, nurse practitioners, PA's and other health professionals.
Keywords: Ambulatory medical care,Chăm sóc người bệnh